Integrating Sexual and Reproductive Health Services Within HIV Services: WHO Guidance - Nathan Ford; Morkor Newman; Sarai Malumo; Lastone Chitembo; Mary E. Gaffield (Frontiers Media S.A., 2021)
Among the 1.9 billion women of reproductive age worldwide in 2019, 1.1 billion need family planning and 270 million have an unmet need for contraception. For women and adolescent girls living with human immunodeficiency virus (HIV), using effective contraception reduces the mother-to-child transmission of HIV by preventing unintended pregnancies and enabling the planning and safer conception of desired pregnancies with optimal maternal and child health outcomes. The World Health Organization (WHO) recommends that sexual and reproductive health services, including contraception, may be integrated within HIV services. Integration is associated with increased offers and uptake of sexual and reproductive health services, including contraception, which is likely to result in improved downstream clinical outcomes. Integrating HIV and sexual and reproductive health services has been found to improve access, the quality of antenatal care and nurse productivity while reducing stigma and without compromising uptake of care. Research is encouraged to identify approaches to integration that lead to better uptake of sexual and reproductive health services, including contraception. Implementation research is encouraged to evaluate different strategies of integration in different health systems and social contexts; such research should include providing contraception, including long-acting contraception, in the context of less frequent clinical and ART refill visits.